THE STATE AND HIDDEN DISCRIMINATION: Islamic Preference and the Future of Religious Harmony in Southeast Asia - Salayan, Irwandra; Masbukin, Masbukin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study critically examines state-facilitated religious favoritism in Indonesia’s plural democratic context, with a particular focus on the Masjid Paripurna program in Pekanbaru and comparative examples from majority non-Muslim regions. Drawing on structural violence (Galtung), symbolic power (Bourdieu), and theories of misrecognition (Honneth) and hegemony (Gramsci), the research reveals how ostensibly neutral administrative practices—budget allocations, permit procedures, and public moral narratives—systematically privilege majority religious groups. These practices manifest as symbolic violence, normalizing exclusion without overt coercion, and placing minority communities in a persistent dilemma of representation: conform to dominant norms or risk marginalization. Through document analysis, limited in‑depth interviews, and thematic reading of policy discourse, the study argues that such favoritism undermines the secular ideals of equity and erodes trust in the state as a neutral arbiter. It calls for a paradigmatic shift toward institutional equity, ensuring that all faith communities enjoy equal access to material resources, symbolic recognition, and participatory governance in Indonesia’s multi‑religious society